(untitled) (Marketing Journal, 2025)
This article analyzes the importance of investments in ensuring the economic competitiveness of the Khorezm region, their structural structure, dynamics and key influencing factors. It also considers the possibilities of stimulating regional economic growt h by improving the investment climate.